Analisis Interaksi Obat Pada Penyakit Ginjal Tahap V (On Hemodialisa) Berdasarkan Resep Di Instalasi Farmasi Rumah Sakit Pelabuhan Jakarta Selama Januari - Juni 2013 - Diana Laila Ramatillah; Stefanus Lukas; Tri Hastuti (STIFARM Padang, 2014)
Drug interactions are interactions that occur when a drug is altered by the effects of other drugs, food, or beverages. Drug interactions can cause a reduction in effects of therapeutic, increasing of toxicity or pharmacological activity that is not expected whereas according to its severity, it is divided into major, moderate and minor. From the results of